Nourishing the alchemical child: metaphors of family life as textual cohesion in the fifteenth-century The Gracious Work - Norja, Sara (Cambridge University Press (CUP), 2025)
English-language alchemical manuscript texts remain under-studied despite their potential for providing new insights into the textual histories of alchemy. In this article, I use close reading of one such Middle English alchemical text, which I name The Gracious Work, to examine how its alchemical metaphors create cohesion among a fragmented whole. This nameless and previously unstudied work, formerly attributed to Roger Bacon (c.1214–92?), is extant in four English-language manuscript witnesses. Three of them are from the late fifteenth century (Cambridge, University Library MS Dd.4.45; Cambridge, Trinity College MS R.14.45; Oxford, Bodleian Library MS Ashmole 1451) and one is from the seventeenth century (MS Ashmole 1452). On the surface, The Gracious Work looks like a typically ‘incoherent’ alchemical text; indeed, although exploring this work’s textual history is beyond the scope of this article, it was probably compiled from several sources. However, the coherence in The Gracious Work comes from its central metaphors – core alchemical metaphors drawn from family life. Metaphors linking alchemical processes and substances to concepts of daily life such as weddings and parenthood ease information transmission in this fragmentary work; in addition, the vagueness of the language acts as a marker of in-group language use.